Estudo sobre a implementação da metodologia BIM (building information modeling) nas regiões centro e Alentejo de Portugal - Machado, P. (2021)
At the international level, the adoption of the BIM (Building Information Modeling) methodology is rapidly expanding and is already a reality in several countries. The level of implementation and maturity differ between different countries. Several governments are encouraging a paradigm shift in the construction sector, looking for this change to promote greater efficiency and productivity. However, for this change to occur, it is necessary to know its level of implementation in order to define the best incentive strategies. In comparison with other countries, Portugal appears to be in an early stage of adopting BIM. This delay is more pronounced in the Center and Alentejo regions, which are the subject of this study. The results can serve to improve strategies for adopting the BIM methodology in the AEC sector in these regions. In this survey, it was found that 73% of respondents have some knowledge of BIM. This result is higher than that obtained in a study carried out in Portugal in 2015, and may be a consequence of the numerous initiatives carried out to disseminate the BIM methodology that occurred between the years 2015 and 2018. In other parameters, there are no significant differences between the results of the two surveys.